PENERAPAN POMPA HIDRAM METODE PARALEL DI DESA PUNGGUK BERINGIN BENGKULU TENGAH - ., Irkhos; ., Suhendra; ., Sukisno (Dharma Raflesia : Jurnal Ilmiah Pengembangan dan Penerapan IPTEKS, 2017)
The program is implemented in Pungguk Beringin Merigi Kelindang Bengkulu Tengah. The purpose of this program is to provide the knowledge and skills of rural communities Pungguk Beringin on utilization Hydraulic ram. Participants were representatives of community activities. The solution provided is the application of Parallel Methods Hydraulic ram. Through this program generated installation Hydraulic ram diameter of 2 inches with 10 liters of effluent water discharge to drain the water to a height of 50 meters by 150 meters. Keywords: Hydraulic ram pump, Parallel Methods, Pungguk Beringin